A unifying theoretical framework for conservation flagships - Jarić, Ivan; Crowley, Sarah L.; Jeschke, Jonathan M.; Arbieu, Ugo; de Oliveira Caetano; Gabriel Henrique; Correia, Ricardo A.; Kamdar, Arjun; Ladle, Richard J.; Mammola, Stefano; Roll, Uri; Veríssimo, Diogo (Elsevier BV, 2025)
Conservation flagships are an effective approach to mobilize support for conservation. The flagship concept has recently been expanded beyond species, to include also fleets, protected areas, ecosystems, individuals, and events. Here, we present a unifying framework of flagship categories and their use, provide a roadmap for flagship selection, and give recommendations for their use in conservation practice. We also propose the flexible encompassing term ‘flagship entity’, broadly defined as a unique and recognizable entity that can be easily communicated for conservation purposes. Flagship entities are characterized by their biological and ecological organization level, temporal state, geographical reach, current level of use, and effectiveness. Flagship selection should be driven by sound knowledge and a clear understanding of the target audience’s conscious and subconscious preferences and its intended use. Further work is needed to evaluate the effectiveness of various flagship categories and concepts, and the positive and negative economic outcomes of flagship strategies.